Hubungan Dukungan Keluarga Dengan Kualitas Hidup Lansia Pada Masa COVID-19 - Tiara Putri Wiraini; Ririn Muthia Zukhra; Yesi Hasneli (HEALTH CARE : JURNAL KESEHATAN, 2021)
The elderly are among those who are vulnerable to Covid-19 transmission due to low immunity and chronic diseases experienced by the elderly. Family support is needed so that the quality of life and health of the elderly are maintained optimally. This study aims to determine the relationship between family support and the quality of life of the elderly during the Covid-19 period. This research is a quantitative study with a descriptive correlation design and a cross sectional approach. The sampling technique was purposive sampling with 125 respondents. The measuring instrument used was the WHOQOL-BREF family support and quality of life questionnaire. The results of this study indicate that family support is in a good category (70.4%) and the quality of life of the elderly is in a good category (89%). The results of statistical tests using fisher's test obtained p value <α (0.05), so it can be concluded that there is a significant relationship between family support and the quality of life of the elderly during the Covid-19 period. The Odd Ratio value of 41,760 shows that elderly people with good family support have a 41,760 times better quality of life. Recommendations for future research address quality of life factors in more domains (eg, physical, psychosocial, social and environmental domains) and include elderly living with a partner / alone into inclusion.